The Ascent of Man - Bronowski, Jacob (London British Broadcasting Corporation, 1975)
Dr Jacob Bronowksi's The Ascent of Man traces the development of human society through our understanding of science. First published in 1973 to accompany the groundbreaking BBC television series, it is considered one of the first works of 'popular science', illuminating the historical and social context of scientific development for a generation of readers. In his highly accessible style, Dr Bronowski discusses human invention from the flint tool to geometry, agriculture to genetics, and from alchemy to the theory of relativity, showing how they all are expressions of our ability to understand and control nature. In this new paperback edition, The Ascent of Man inspires, influences and informs as profoundly as ever.
Include Illustrations, Bibliography and Index.
Keywords: Science -- Science--Philosophy -- Human beings